2005
DOI: 10.1074/jbc.m413308200
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Receptor Activation Depends on Critical Cysteine Residues in Its Fibronectin Type III Subdomains

Abstract: The leptin receptor (LR) complex is composed of a single subunit belonging to the class I cytokine receptor family and exists as a preformed complex. The extracellular portion contains two cytokine receptor homology (CRH) domains, separated by an Ig-like domain and followed by two membrane-proximal fibronectin type III (FNIII) domains. The mechanisms underlying ligandinduced receptor activation are still poorly understood. LRs can exist as disulfide-linked dimers at the cell surface, even in the absence of lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…All isoforms except LEPR-e have a similar extracellular ligand-binding domain, but differ in their intracellular domains. Recently, it was reported that leptin receptor activation depends on critical cysteine residues located in the extracellular domain (Zabeau et al, 2005). In connection with this, we found that ascorbic acid partially recovered the NO-mediated inhibition (almost complete inhibition by accumulated NOx concentration for 30 min of 300 μM) of leptin signaling (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…All isoforms except LEPR-e have a similar extracellular ligand-binding domain, but differ in their intracellular domains. Recently, it was reported that leptin receptor activation depends on critical cysteine residues located in the extracellular domain (Zabeau et al, 2005). In connection with this, we found that ascorbic acid partially recovered the NO-mediated inhibition (almost complete inhibition by accumulated NOx concentration for 30 min of 300 μM) of leptin signaling (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Couturier and Jockers (37) used a bioluminescence resonance energy transfer assay to show that 60% of the LR population exists as dimers and that leptin induces conformational reorganization of these preformed LR complexes. At least part of the LR population exists as disulfide-linked dimers at the cell surface, even in the absence of leptin, and both the isolated CRH2 domain and the two fibronectin type III domains can form disulfidelinked dimers (13). In the hexameric model complex, the C termini of the CRH2 domains of LR1 and LR2 approach each other.…”
Section: Discussionmentioning
confidence: 99%
“…2) Ligand-independent clustering of the LR has been demonstrated in solution (13,27) and at the cell surface (13,(37)(38)(39). Couturier and Jockers (37) used a bioluminescence resonance energy transfer assay to show that 60% of the LR population exists as dimers and that leptin induces conformational reorganization of these preformed LR complexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two WS!WS residues suggested to contribute to ligand-recognition in cytokine receptors, and the cytokine receptor homology (CRH) domains, implicated in leptin binding, were well conserved. The C residues characteristic of the fibronectin type II modules (Zabeau et al 2005) are indicated. Thus, despite the low sequence similarity among these sequences, all of the known functional motifs and domains of LEPR were conserved in terms of both sequence and position.…”
Section: Comparison Of Human Chicken and Xenopus Lepr Amino Acid Sementioning
confidence: 99%